Detection and Understanding of Natural CO2 Releases in KwaZulu-Natal, South Africa. (July 2017) - Johnson, G.; Hicks, N.; Bond, C.E.; Gilfillan, S.M.V.; Jones, D.; Kremer, Y.; Lister, R.; Nkwane, M.; Maupa, T.; Munyangane, P.; Robey, K.; Saunders, I.; et al.
Abstract: Natural carbon dioxide (CO2 ) emanates from a number of sites along a N-S trend that coincides with a mapped fault near the village of Bongwana in KwaZulu-Natal, South Africa. In addition to the natural CO2 seeps a groundwater well drilled on a farm in Bongwana encountered CO2 and now leaks. Thus the Bongwana sites provide excellent analogues for failed CO2 storage under the two primary leakage scenarios; 1) abrupt leakage through injection well failure or leakage up an abandoned well, and 2) gradual leakage, through undetected faults, fractures or wells. Here we present results from preliminary fieldwork undertaken in September 2015.